(untitled) - Sidhu, Waheguru Pal Singh (Boulder, 2003)
The hardline view of Sino-Indian relations found in the published reports of Indian and Chinese security analysts is often at considerable odds with the more tempered opinions those same analysts express in private interviews and conversations. What is the reality of the increasingly important security relationship between the two countries? The authors of this new study address that question in depth. Sidhu and Yuan explore a range of key issues, including mutual distrust and misperception (perhaps the most important factor), the undemarcated border, the status of Tibet and Sikkim, trade, the tussle over various nonproliferation treaties, terrorism, the regional roles of the U.S. and Pakistan, and the impact of domestic public opinion and special interests. They do see a trend toward a more pragmatic approach in Beijing and New Delhi to managing differences and broadening the agenda of common interests. Nevertheless, they conclude, significant obstacles remain to the amicable relationship necessary for regional peace and stability, posing a daunting challenge to policymakers in these two rising powers.
Keywords: Foreign relations,Foreign relations,Foreign relations; 1976-,1984-; China,India,China,India